AGNP Consensus Guidelines for Therapeutic Drug Monitoring in Psychiatry: Update 2011 - Hiemke, C.; Baumann, P.; Bergemann, N.; Conca, A.; Dietmaier, O.; Egberts, K.; Fric, M.; Gerlach, M.; Greiner, C.; Gründer, G.; Haen, E.; Havemann-Reinecke, U.; Jaquenoud Sirot, E.; Kirchherr, H.; Laux, G.; Lutz, U. C.; Messer, T.; Müller, M. J.; Pfuhlmann, B.; Rambeck, B.; Riederer, P.; Schoppek, B.; Stingl, J.; Uhr, M.; Ulrich, S.; Waschgler, R.; Zernig, G. (Pharmacopsychiatry, 2011)
Therapeutic drug monitoring (TDM), i. e., the quantification of serum or plasma concentrations of medications for dose optimization, has proven a valuable tool for the patient-matched psychopharmacotherapy. Uncertain drug adherence, suboptimal tolerability, non-response at therapeutic doses, or pharmacokinetic drug-drug interactions are typical situations when measurement of medication concentrations is helpful. Patient populations that may predominantly benefit from TDM in psychiatry are children, pregnant women, elderly patients, individuals with intelligence disabilities, forensic patients, patients with known or suspected genetically determined pharmacokinetic abnormalities or individuals with pharmacokinetically relevant comorbidities. However, the potential benefits of TDM for optimization of pharmacotherapy can only be obtained if the method is adequately integrated into the clinical treatment process. To promote an appropriate use of TDM, the TDM expert group of the Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie (AGNP) issued guidelines for TDM in psychiatry in 2004. Since then, knowledge has advanced significantly, and new psychopharmacologic agents have been introduced that are also candidates for TDM. Therefore the TDM consensus guidelines were updated and extended to 128 neuropsychiatric drugs. 4 levels of recommendation for using TDM were defined ranging from “strongly recommended” to “potentially useful”. Evidence-based “therapeutic reference ranges” and “dose related reference ranges” were elaborated after an extensive literature search and a structured internal review process. A “laboratory alert level” was introduced, i. e., a plasma level at or above which the laboratory should immediately inform the treating physician. Supportive information such as cytochrome P450 substrate- and inhibitor properties of medications, normal ranges of ratios of concentrations of drug metabolite to parent drug and recommendations for the interpretative services are given. Recommendations when to combine TDM with pharmacogenetic tests are also provided. Following the guidelines will help to improve the outcomes of psychopharmacotherapy of many patients especially in case of pharmacokinetic problems. Thereby, one should never forget that TDM is an interdisciplinary task that sometimes requires the respectful discussion of apparently discrepant data so that, ultimately, the patient can profit from such a joint effort.
Keywords: consensus guidelines; drug analysis; pharmacokinetics; psychotropic drugs; reference ranges; therapeutic drug monitoring; therapeutic window